IMPACT OF ADDING OXYGENATES TO DIESEL FUEL ON ENGINE’S PERFORMANCE AND EMISSIONS (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
??investigation of performance and emission of conventional a four-stroke, single-cylinder direct injection (DI) diesel engine at variable engine speed range from (1500 to 3000 rpm), carried out at steady-state tests conditions with diesel fuel and biodiesel which is produced from sun flower oil mixed with the higher alcohol. The blends effects on the performance and emission for the blended fuels measured and compared. 10% and 15% of Pentanol, Octanol added to the biodiesel blended with diesel for various test conditions. The experimental results showed an approximately 2–9% increase in the brake-specific fuel consumption (BSFC) for the prepared blends of pentanol and octanol due to the lower heating value (LHV), with higher brake thermal efficiency compared to diesel fuel. With expressively reduction of (9.8-21% vol.) in carbon monoxide (CO), and total unburned hydrocarbons (THCs) of (65-78.3% ppm), and nitric oxides (NOx) (44.4–52.9% ppm). The combustion analyses showed that the addition of biodiesel to conventional diesel fuel decreased the ignition delay and reduced the properties. These results indicated that biodiesel and higher alcohol could be used without any engine modifications as an alternative and environmentally friendly fuel.